Survival assessment in extremely preterm neonates in a middle-income setting - Rodriguez-Sibaja, Maria J.; Herrera-Ortega, Olivo; Lumbreras-Marquez, Mario I.; Morales-Barquet, Deneb; Acevedo-Gallegos, Sandra; Copado-Mendoza, Yazmin; Camarena-Cabrera, Dulce M.; Gallardo-Gaona, Juan M. (Frontiers in Pediatrics, 2025)
IntroductionGlobally, an estimated 15.1 million preterm neonates are born annually, with 1% classified as extremely preterm (i.e., <28.0 weeks of gestation). The survival and outcomes of this vulnerable population are influenced by multiple factors, particularly gestational age, birth weight, and available medical resources. This study aimed to describe the hospital discharge survival of extremely preterm infants born in a middle-income setting. As a secondary objective, we assessed the neonatal morbidity associated with this group.Material and methodsIn this cross-sectional study of singleton pregnancies, neonatal survival following extremely preterm birth was determined using three different denominators and expressed as prevalence (i.e., percentages): (1) the total number of extremely preterm births, including intrapartum fetal deaths; (2) the total number of all live births, including neonatal deaths in the delivery room, and (3) the total number of preterm neonates admitted to the neonatal intensive care unit (NICU). Neonatal morbidity was assessed as a secondary outcome.ResultsThere were no live births between 22.0 and 23.6 weeks of gestation. Overall mortality decreased with increasing gestational age, from 100% (22/22) at <24.0 weeks of gestation to 87% (14/16), 42% (16/38), and 21% (11/52) at a gestational age of 25, 26, and 27 weeks, respectively. The survival rate to NICU discharge among extremely preterm infants was 49% (65/132), 67% (65/97), and 69% (65/93), depending on whether survival was calculated based on all births, all live births, or NICU admissions, respectively. None of the neonates born before 24.6 weeks of gestation survived to discharge. Notably, 97.0% of NICU survivors were diagnosed with major morbidity.ConclusionThe survival rate at NICU discharge exceeds 50% from 26 weeks onwards in a middle-income setting. Importantly, survival rates varied significantly depending on the denominator used, highlighting the need to carefully select inclusion criteria in neonatal survival analyses. Notably, survival after extremely preterm birth was associated with significant morbidity.